TNFα expressed on the surface of microparticles modulates endothelial cell fate in rheumatoid arthritis - Barbati, Cristiana (Arthritis Res Ther, 2018)
BACKGROUND: Rheumatoid arthritis (RA) is associated with a high prevalence of atherosclerosis. Recently increased levels of microparticles (MPs) have been reported in patients with RA. MPs could represent a link between autoimmunity and endothelial dysfunction by expressing tumor necrosis factor alpha (TNFα), a key cytokine involved in the pathogenesis of RA, altering endothelial apoptosis and autophagy. The aim of this study was to investigate TNFα expression on MPs and its relationship with endothelial cell fate. METHODS: MPs were purified from peripheral blood from 20 healthy controls (HC) and from 20 patients with RA, before (time (T)0) and after (T4) 4-month treatment with etanercept (ETA). Surface expression of TNFα was performed by flow cytometry analysis. EA.hy926 cells, an immortalized endothelial cell line, were treated with RA-MPs purified at T0 and at T4 and also, with RA-MPs in vitro treated with ETA. Apoptosis and autophagy were then evaluated. RESULTS: RA-MPs purified at T0 expressed TNFα on their surface and this expression significantly decreased at T4. Moreover, at T0 RA-MPs, significantly increased both apoptosis and autophagy levels on endothelial cells, in a dose-dependent manner. RA-MPs did not significantly change these parameters after 4 months of in vivo treatment with ETA. CONCLUSIONS: Our data demonstrate that MPs isolated from patients with RA exert a pathological effect on endothelial cells by TNFα expressed on their surface. In vivo and in vitro treatment with ETA modulates this effect, suggesting anti-TNF therapy protects against endothelial damage in patients with RA. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13075-018-1768-8) contains supplementary material, which is available to authorized users.